2017
DOI: 10.1002/glia.23229
|View full text |Cite
|
Sign up to set email alerts
|

Lineage tracing reveals dynamic changes in oligodendrocyte precursor cells following cuprizone‐induced demyelination

Abstract: The regeneration of oligodendrocytes is a crucial step in recovery from demyelination, as surviving oligodendrocytes exhibit limited structural plasticity and rarely form additional myelin sheaths. New oligodendrocytes arise through the differentiation of platelet-derived growth factor receptor α (PDGFRα) expressing oligodendrocyte progenitor cells (OPCs) that are widely distributed throughout the CNS. Although there has been detailed investigation of the behavior of these progenitors in white matter, recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
73
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 45 publications
17
73
0
Order By: Relevance
“…Six weeks after cuprizone ingestion, demyelination occurs globally, but it is most prominent in the corpus callosum and posterior cerebellar peduncles and is referred to as “acute demyelination.” Acute demyelination is followed by spontaneous remyelination, when a cuprizone diet is replaced by normal chow. The remyelination process is dependent on OPC maturation, and the reappearance of myelin in white matter is more obvious than in gray matter, where proliferation and differentiation of OPC is prolonged in cuprizone‐induced demyelination (Baxi et al, ). On the contrary, prolonged cuprizone intoxication (more than 12 weeks) results in a constrained spontaneous remyelination process: “chronic demyelination.” During chronic stages of the disease, apoptosis of oligodendrocytes occurs in a caspase‐3–independent manner (Gudi, Gingele, Skripuletz, & Stangel, ).…”
Section: Toxin‐induced Demyelination Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six weeks after cuprizone ingestion, demyelination occurs globally, but it is most prominent in the corpus callosum and posterior cerebellar peduncles and is referred to as “acute demyelination.” Acute demyelination is followed by spontaneous remyelination, when a cuprizone diet is replaced by normal chow. The remyelination process is dependent on OPC maturation, and the reappearance of myelin in white matter is more obvious than in gray matter, where proliferation and differentiation of OPC is prolonged in cuprizone‐induced demyelination (Baxi et al, ). On the contrary, prolonged cuprizone intoxication (more than 12 weeks) results in a constrained spontaneous remyelination process: “chronic demyelination.” During chronic stages of the disease, apoptosis of oligodendrocytes occurs in a caspase‐3–independent manner (Gudi, Gingele, Skripuletz, & Stangel, ).…”
Section: Toxin‐induced Demyelination Modelsmentioning
confidence: 99%
“…On the contrary, prolonged cuprizone intoxication (more than 12 weeks) results in a constrained spontaneous remyelination process: “chronic demyelination.” During chronic stages of the disease, apoptosis of oligodendrocytes occurs in a caspase‐3–independent manner (Gudi, Gingele, Skripuletz, & Stangel, ). Systemic application of cuprizone generates demyelination in the corpus callosum; however, a loss of myelin is also observed in the cortex, hippocampus, and cerebellum (Baxi et al, ; Kipp, Clarner, Dang, Copray, & Beyer, ).…”
Section: Toxin‐induced Demyelination Modelsmentioning
confidence: 99%
“…In the same line, cuprizone‐treated animals have shown that, despite the comparable density of OPC in gray and white matter, the temporal dynamics of OPC differentiation varies significantly between these zones. While OPC rapidly repopulates the CC and mature into CC1‐expressing OL, OPC differentiation in the CTX occurs more slowly and is less complete, resulting in a delay in remyelination relative to the CC (Baxi et al, ). The differences observed in the dynamics of remyelination between gray and white matter can be explained by different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These cells persist in the adult CNS parenchyma, where they comprise about 5% of all CNS cells [2], and can serve as a rapidly responding reservoir for new OLs in case of demyelination [1,3,4]. In intact adult nervous tissue, NG2 glia can also be engaged in proliferation and maturation to sustain a certain degree of oligodendrogenesis [5,6] and myelin plasticity [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In view of achieving neuronal replacement in the adult CNS, the idea that NG2 glia can be the source for new neurons is particularly attractive because of their abundance and ubiquitous distribution. However, this has been proven true in vivo only upon specific cell reprogramming approaches, and clear evidence that adult NG2 glia spontaneously contribute to parenchymal neurogenesis or astrogliogenesis is lacking [4,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%